Characterization of the Mycobacterium bovis Restriction Fragment Length Polymorphism DNA Probe pUCD and Performance Comparison with Standard Methods - O'Brien, Rory (American Society for Microbiology, 2000)
In this study, the newly described Mycobacterium bovis restriction fragment length polymorphism (RFLP) typing probe pUCD was characterized by sequence analysis and the previously observed polymorphic banding pattern was reproduced with a combination of three oligonucleotide probes in a single, mixed hybridization. In addition, the ability of pUCD to distinguish between 299 M. bovis isolates from the Republic of Ireland was assessed in relation to established methods and a statistical function for objective comparison of RFLP probes was derived. It was found that typing with pUCD alone produced greater discrimination between M. bovis isolates than typing with the commonly used mycobacterial DNA probes IS6110, PGRS, and DR and also by the spoligotyping technique. pUCD and DR in combination produced the highest level of discrimination while maintaining a high level of concordance with known epidemiological data relating to the samples. The reduction of pUCD to the level of oligonucleotides should in future allow pUCD and DR to be included together in a mixed hybridization, thus producing a high level of M. bovis strain type discrimination from a single round of RFLP analysis.